2016
DOI: 10.18632/oncotarget.6963
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non-coding RNA TP73-AS1 inhibits cell proliferation and induces apoptosis in esophageal squamous cell carcinoma

Abstract: Recent studies have shown that long non-coding RNAs (lncRNAs) are involved in a variety of biological processes and diseases in humans, including cancer. Our study serves as the first comprehensive analysis of lncRNA TP73-AS1 in esophageal cancer. We utilized a lncRNA microarray to analyze the expression profile of lncRNAs in esophageal squamous cell carcinoma. Our results show that lncRNA TP73-AS1 and BDH2 levels are generally upregulated in esophageal cancer tissues and are strongly correlated with tumor loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 39 publications
(33 reference statements)
6
85
0
Order By: Relevance
“…TP73-AS1 was associated with cell proliferation and tumor progression. TP73-AS1 knockdown suppressed cancer cell proliferation and induced apoptosis in esophageal squamous cell carcinoma [22] and knockdown of TP73-AS1 also induced apoptosis in glioblastoma cells [27]. In ccRCC, we also identified that TP73-AS1 induced cell proliferation, migration and inhibits cell apoptosis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…TP73-AS1 was associated with cell proliferation and tumor progression. TP73-AS1 knockdown suppressed cancer cell proliferation and induced apoptosis in esophageal squamous cell carcinoma [22] and knockdown of TP73-AS1 also induced apoptosis in glioblastoma cells [27]. In ccRCC, we also identified that TP73-AS1 induced cell proliferation, migration and inhibits cell apoptosis.…”
Section: Discussionmentioning
confidence: 68%
“…Thereafter, it was reported that TP73-AS1 was generally upregulated in esophageal cancer tissues and was strongly associated with malignant level in clinical samples. Besides, TP73-AS1 knockdown could enhance the chemosensitivity of esophageal cancer cells to 5-FU and cisplatin [22]. These opposite changes indicated its heterogeneity in different cancer.…”
Section: Discussionmentioning
confidence: 95%
“…They are associated with a variety of biological processes, including cell proliferation, cell cycle, differentiation and apoptosis, primarily by the regulation of gene expression through chromatin remodeling, RNA maturation, transport and protein synthesis (8). Advances in the depth and quality of transcript me sequencing have revealed a range of lncRNAs classes dysregulated in various human diseases, particularly cancer (9)(10)(11). H19 is a member of a highly-conserved cluster of imprinted genes, and was the first lncRNA to be associated with cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, MIAT could be directed at a novel and hopeful biomarker and therapeutic target for ERpositive BC.3.1.7 | LncRNA TP73-AS1/miR-200a/mRNAs TFAM and ZEB1There are some reports that P73 antisense RNA 1T (TP73-AS1) lncRNA is involved in several types of tumors through regulating the ABDOLLAHZADEH ET AL. | 10087 apoptosis by influencing the expression of P53-related antiapoptotic genes(Hui-rui & Jun-dong, 2016;Zang et al, 2016). A new study byYao et al (2017) revealed the oncogene activity of lncRNA TP73-AS1 in BC thorough functioning as a sponging ceRNA on miR-200a for activating the TFAM mRNA.…”
mentioning
confidence: 99%